2013
DOI: 10.1177/1533317513488925
|View full text |Cite
|
Sign up to set email alerts
|

The Neglected Role of Histamine in Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by beta-amyloid plaques accumulation and cognitive impairment. Both environmental factors and heritable predisposition have a role in AD. Histamine is a biogenic monoamine that plays a role in several physiological functions, including induction of inflammatory reactions, wound healing, and regeneration. The Histamine mediates its functions via its 4 G-protein-coupled Histamine H1 receptor (H1R) to histamine H1 receptor (H4R). The histamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 97 publications
1
23
0
Order By: Relevance
“…Reduced levels of histamine and urocanic acid, as well as increased 1-methylhistamine (Table 1) Alzheimer's disease (Naddafi and Mirshafiey, 2013). Thereby, AD has been previously associated with a loss of histaminergic neurons in the tuberomamillary nucleus (Nakamura et al, 1993) , 1998), in agreement with our findings in serum samples.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Reduced levels of histamine and urocanic acid, as well as increased 1-methylhistamine (Table 1) Alzheimer's disease (Naddafi and Mirshafiey, 2013). Thereby, AD has been previously associated with a loss of histaminergic neurons in the tuberomamillary nucleus (Nakamura et al, 1993) , 1998), in agreement with our findings in serum samples.…”
Section: Discussionsupporting
confidence: 82%
“…Reduced levels of histamine and urocanic acid, as well as increased 1-methylhistamine (Table 1) Alzheimer's disease (Naddafi and Mirshafiey, 2013). Thereby, AD has been previously associated with a loss of histaminergic neurons in the tuberomamillary nucleus (Nakamura et al, 1993), leading to a decline of histamine levels in different brain areas (Mazurkiewicz-Kwilecki and Nsonwah, 1989; Panula 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 et al, 1998), in agreement with our findings in serum samples.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, H3 receptors have also been implicated in suppressing histamine release in the brain. Therefore, pharmacological agents known to antagonize the H3 receptor and to regulate the H2 receptor have been proposed as promising treatment avenues for patients with Alzheimer disease [68]. Likewise, reduced histamine levels have also been demonstrated after bilateral carotid artery occlusion in rats, suggesting a potential role in vascular dementia [69].…”
mentioning
confidence: 99%
“…Importantly, we found that the inhibition of the H 3 R does not alter the motivational state of mice to drink nonalcohol tastants such as saccharin, which is a critical issue from a potential therapeutic development perspective. Our findings therefore suggest that antagonists of the H 3 R pathway, which are actively being developed for the treatment of several psychiatric disorders [24,[57][58][59][60], are potential pharmacological candidates that could be developed for the treatment of alcohol use and abuse disorders.…”
Section: Resultsmentioning
confidence: 93%